Metode Power Control sebagai Manajemen Interferensi pada Komunikasi Device to Device - Anggun Fitrian Isnawati; Sholihah Larasati; Indak Danil Mabar (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2021)
Today’s communication technology development has entered the 5th generation (5G), where one of the solutions offered is device to device (D2D) communication. The scheme used in this study was cooperative D2D with Mobile User Equipment (MUE) located far from the eNodeB (eNB). The D2D User Equipment (DUE) served as a relay that helped MUE to improve service quality. The effect caused by D2D communication was interference. Therefore, the power control method was used to overcome this problem. This study used three comparative simulations, namely Without Power Control, using Power Control 1, and using Power Control 2. The scheme used in Power Control 1 was a fixed power control, while Power Control 2 used an adaptive power control. Using the Cumulative Distribution Function (CDF), Power Control 1 scheme could improve SINR by 0.124 dB for downlink and 0.0814 dB for uplink. Meanwhile, Power Control 2 scheme could increase SINR by 0.0316 dB for downlink and 0.0627 for uplink. Based on the final results related to SINR, throughput, and CDF, the Power Control 1 method has better results than the Power Control 2 method.